Membrane Proteomics of Arabidopsis Glucosinolate Mutants cyp79B2/B3 and myb28/29 - Mostafa, Islam; Yoo, Mi-Jeong; Zhu, Ning; Geng, Sisi; Dufresne, Craig; Abou-Hashem, Maged; El-Domiaty, Maher; Chen, Sixue (Frontiers in Plant Science, 2017)
Glucosinolates (Gls) constitute a major group of natural metabolites represented by three major classes (aliphatic, indolic and aromatic) of more than 120 chemical structures. In our previous work, soluble proteins and metabolites in Arabidopsis mutants deficient of aliphatic (myb28/29) and indolic Gls (cyp79B2B3) were analyzed. Here we focus on investigating the changes at the level of membrane proteins in these mutants. Our LC/MS-MS analyses of tandem mass tag (TMT) labeled peptides derived from the cyp79B2/B3 and myb28/29 relative to wild type resulted in the identification of 4673 proteins, from which 2171 are membrane proteins. Fold changes and statistical analysis showed 64 increased and 74 decreased in cyp79B2/B3, while 28 increased and 17 decreased in myb28/29. As to the shared protein changes between the mutants, one protein was increased and eight were decreased. Bioinformatics analysis of the changed proteins led to the discovery of three cytochromes in glucosinolate molecular network (GMN): cytochrome P450 86A7 (At1g63710), cytochrome P450 71B26 (At3g26290) and probable cytochrome c (At1g22840). CYP86A7 and CYP71B26 may play a role in hydroxyl-indolic Gls production. In addition, flavone 3'-O-methyltransferase 1 represents an interesting finding in this study as it is likely to participate in the methylation process of the hydroxyl-indolic Gls to form methoxy-indolic Gls. The analysis also revealed additional new nodes in the GMN related to stress and defense activity, transport, photosynthesis and translation processes. Gene expression and protein levels were found to be correlated in the cyp79B2/B3, but not in the myb28/29.